Anteseden Kepuasan Pelanggan terhadap Niat Beli Ulang - Shafira Fitri Cahyaning Ratri; Anas Hidayat (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
This study aims to analyze the antecedents of repurchase intention on Apples smartphones. The population used in this study is the Indonesian people. While the sample taken from this study was 250 respondents. The data used in this research is primary data via google form which is distributed online through social media. The sampling technique used in this study was Convienence Sampling. The data were processed by SEM analysis using the AMOS program. Data variables used in this study consisted of variables of service quality, perceived usefulness, customer satisfaction and repurchase intention. The results of the data analysis conducted indicate that there is a positive and significant influence on service quality variables on perceived usefulness, service quality on customer satisfaction, service quality on repurchase intentions, perceived usefulness on customer satisfaction, perceived usefulness on repurchase intentions and satisfaction. customers against repurchase intentions.